Bertrand-Edgeworth Competition in Experimental Markets - Kruse, Jamie Brown; Rassenti, Stephen; Reynolds, Stanley S.; Smith, Vernon L. (Econometrica, 1994)
The Bertrand-Edgeworth model describes competition among price setting sellers with production capacity constraints. The authors report on laboratory experiments that permit evaluation of different theories of Bertrand-Edgeworth competition: competitive pricing, Edgeworth cycles in prices, mixed strategy Nash equilibrium pricing, and tacit collusion. Each of the theories helps to explain some aspects of the data. However, none of these theories are completely consistent with the data. In relative terms, the Edgeworth cycle theory provides better predictions of key aspects of the data than the other theories. Coauthors are Stephen Rassenti, Stanley S. Reynolds, and Vernon L. Smith. Copyright 1994 by The Econometric Society.